Creation of a Perioperative Medicine Curriculum for an Anesthesiology Residency Program - Tetzlaf, John E. (J Educ Perioper Med, 1999)
Because of the increasing expansion of the practice of anesthesiology beyond the borders of the operating room, there is attention being paid to Perioperative Medicine (PM) within anesthesiology training programs. With the elements of PM incorporated into the newest requirements for anesthesiology residency programs by the Residency Review Committee (RRC) for Anesthesiology of the American College of Graduate Medical Education (ACGME), programs are obliged to develop PM curriculum. At the Cleveland Clinic, a PM curriculum was created from existing, diverse elements of the clinical practice. Clinical supervision of the Pre-Anesthesia testing center, the Same-Day-Surgery unit, In-House Consultation and the Post-Anesthesia Care Unit were combined into a single teaching service. A didactic curriculum was created, resident function within these units was defined, and weekly teaching sessions were created. The result has been increased clinical teaching of PM, satisfaction of RRC requirements, and improved opportunity for resident learning in these areas. Residents have rated PM within the top 10% of rotations for the first two years of existence. We conclude that a combined service is an excellent approach to the creation of a PM curriculum.